Real-world effectiveness and safety of CDK4/6i in elderly and BIPOC patients with HR+/HER2- advanced/metastatic breast cancer: an updated systematic literature review - Harbeck, Nadia; Brufsky, Adam; Grace Rose, Chloe; Korytowsky, Beata; Chen, Connie; Tantakoun, Krista; Jazexhi, Endri; Nguyen, Do Hoang Vien; Bartlett, Meaghan; Samjoo, Imtiaz A.; Pluard, Timothy (Frontiers in Oncology, 2025)
Background and aimThe HR-positive/HER2-negative (HR+/HER2-) advanced/metastatic breast cancer (a/mBC) treatment landscape has advanced with cyclin-dependent kinase 4/6 inhibitors (CDK4/6i), yet outcome disparities persist, particularly among older patients and black, indigenous, and people of color (BIPOC) communities. Emerging real-world evidence (RWE) since 2021 highlights the need for this updated systematic literature review.MethodsSearches were conducted in MEDLINE®, Embase®, and Cochrane Databases (07/06/2019–01/09/2024) and key congress proceedings (2020–2024). Studies on CDK4/6i treatment in elderly and BIPOC patients with ≥100 participants and details on therapy line and CDK4/6i type were included. Key outcomes for synthesis were effectiveness, treatment patterns, and safety.ResultsThis review included 23 unique studies. In comparisons of CDK4/6is among elderly patients, palbociclib and ribociclib demonstrated similar effectiveness, whereas data for abemaciclib were limited. These findings aligned with single-arm studies and CDK4/6i versus endocrine therapy (ET) comparisons, which demonstrated superior survival benefits for CDK4/6is over ET alone in both elderly and BIPOC subpopulations. Despite higher discontinuation rates and neutropenia in both subpopulations, survival outcomes remained unaffected in studies assessing effectiveness and tolerability.ConclusionsThis review highlights that CDK4/6is are effective and well-tolerated in elderly and BIPOC patients with HR+/HER2− a/mBC. It also underscores the expanding body of RWE supporting CDK4/6is, highlighting their global use and key role in guiding clinical decisions, particularly for patient subpopulations underrepresented in clinical trials.